Dynamics of irregularly shaped cometary particles subjected to outflowing gas and solar radiative forces and torques. Issue 4 (27th December 2021) - Moreno, Fernando; Guirado, Daniel; Muñoz, Olga; Zakharov, Vladimir; Ivanovski, Stavro; Fulle, Marco; Rotundi, Alessandra; Frattin, Elisa; Bertini, Ivano
ABSTRACT: The dynamics of irregularly shaped particles subjected to the combined effect of gas drag and radiative forces and torques in a cometary environment is investigated. The equations of motion are integrated over distances from the nucleus surface up to distances where the gas drag is negligible. The aerodynamic forces and torques are computed assuming a spherically symmetric expanding gas. The calculations are limited to particle sizes in the geometric optics limit, which is the range of validity of our radiative torque calculations. The dynamical behaviour of irregular particles is quite different to those exhibited by non-spherical but symmetric particles such as spheroids. An application of the dynamical model to comet 67P/Churyumov–Gerasimenko, the target of the Rosetta mission, is made. We found that, for particle sizes larger than ∼10 μm, the radiative torques are negligible in comparison with the gas-driven torques up to a distance of ∼100 km from the nucleus surface. The rotation frequencies of the particles depend on their size, shape, and the heliocentric distance, while the terminal velocities, being also dependent on size and heliocentric distance, show only a very weak dependence on particle shape. The ratio of the sum of the particles projected areas in the sun-to-comet direction to that of the sum of the particles projected areas in any direction perpendicular to it is nearly unity, indicating that the interpretation of the observed u-shaped scattering phase function by Rosetta /OSIRIS on comet 67P coma cannot be linked to mechanical alignment of the particles.